Sepuluh Faktor agar Menjadi Guru yang Dicintai oleh Siswanya - Yazidul Busthomi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2020)
Becoming a teacher is truly noble work. He is responsible for not only making human children smart in the field of science but also good morals in this life. A human child who at first did not understand anything, before a teacher was educated to understand life better and know the world. On his shoulders is the duty and responsibility of the future survival of more intelligent and confronting generations. So noble the work of a teacher and how heavy the duties and responsibilities of being a teacher. This is why not everyone can become a successful teacher. Only certain people who have a love for children or students and are highly dedicated to the world of education are able to become a teacher. This is the personality of a teacher who is both teachings and educating in front of his students, the figure of a favorite teacher who is loved by his students. The ten factors for becoming a teacher that is loved by their students are as follows: 1. Close to students, 2. Building a pleasant atmosphere, 3. Being able to act as a second parent, 4. Being friends in learning, 5. Personality deserves to be copied, 6 Be affectionate, 7. Be patient in teaching, 8. Can make laugh, 9. Liberator for students, 10. I can be a listener and mediator.